PROPER TIME IN TECHNICAL SCIENCES AND ALTERNATIVE NOTIONS FOR THE FORCE, MECHANICAL WORK AND HEAT - ALEXEI MAFTULEAC (Journal of Engineering Studies and Research)
The notion of proper (localized) time is one of the more important in the theory of relativity and is often used to explain phenomena that occur in conditions of high speeds or gravitation. In this paper, on the basis of the concept of proper (localized) time we tried to explain the functioning of simple mechanisms as a change in their space/time relationships, and to consider from another point of view some notions of physics (mechanics). A hypothesis about space and time equivalence and their mutual compensating change in every phenomenon that occurs, has been proposed. This hypothesis is substantiated with formulas and data from literature. This article may be of interest to the physicists and engineers.